Non-linear surges and extreme wind-waves in Port Phillip Bay under existing and future mean sea levels - Tran, Huy Quang; Ayala Cruz, Franklin; McCarroll, Jak; Babanin, Alexander (Frontiers in Marine Science, 2024)
Introduction This study investigates non-linear surges and extreme wind-wave patterns in Port Phillip Bay (PPB), Victoria, Australia, under both current and projected mean sea level (MSL) scenarios. The research aims to understand the potential impacts of increasing MSL on extreme surges and wind-waves, utilising a combined wave-circulation modelling system (SCHISM-WWMIII). Methods This validated coupled model was employed to simulate 32 years of hindcasts (1990-2022) applied to five distinct MSL scenarios: existing, 0.5 m, 0.8 m, 1.1 m, and 1.4 m. Modelled data were extracted from 24 different stations in the bay at a depth of 2 m to analyse the impacts of increasing MSL on extreme surges and wind-waves. Results Under the current scenario, the results indicate that both surges and wave patterns are significantly influenced by seasonal wind patterns. In the context of rising MSL, the research reveals that while surges exhibit a degree of resilience to changes in MSL, the wave field is more vulnerable to such variations. The non-linear response of the wave field to increasing MSL further complicates the scenario. For instance, there is an unequal response in the median of the annual maximum significant wave height (Hs) corresponding to the rising MSL from 0 m to 0.5 m and from 0.5 m to 0.8 m, which is expected due to wave breaking triggered by changes in water depth. Specifically, the median annual maximum Hs at 12 locations remains unchanged when MSL increases from 0 m to 0.5 m. However, increasing MSL from 0.5 m to 0.8 m increases the median annual maximum Hs by up to 0.36 m, accounting for 70% of the total increase in the median annual maximum Hs when MSL rises from 0 m to 1.4 m at the same locations. Discussion The study found that intensification in the median of annual maximum Hs occurs only in locations where the values exceed 1.0 m. This suggests that areas with higher extreme Hs values are more prone to experiencing significant variations. In contrast, stations with a median annual maximum Hs below the 1.0 m threshold exhibit only minor increases in the annual maximum Hs. These findings highlight the complex and non-linear nature of the wave field's response to rising MSL and emphasise the importance of considering local conditions when assessing the impacts of sea level rise on coastal regions.